2021
DOI: 10.3390/ijms22116149
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of a Low-Protein High-Carbohydrate Diet on Mature Female and Male, and Neomale Rainbow Trout

Abstract: Rainbow trout are considered as a poor user of dietary carbohydrates, displaying persistent postprandial hyperglycaemia when fed a diet containing high amounts of carbohydrates. While this phenotype is well-described in juveniles, less attention was given to broodstock. Our objective was to assess for the first time the short-term consequences of feeding mature female and male, and neomale trout with a low-protein high-carbohydrate diet on glucose and lipid metabolism. Fish were fed for two days with a diet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…While this feature is well-described in juveniles less attention is given to rainbow trout broodstocks and especially neomales that are used to produce all-female population. In a previous study we were able to demonstrate that a short carbohydrate intake (two-day feeding) did not induce specific metabolic changes in the liver of females, males and neomales broodstocks [13]. Moreover, we also demonstrated that neomales displayed more pronounced modifications of glucose and lipid metabolisms in response to nutritional status or HC diet compared to both females and males broodstocks.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…While this feature is well-described in juveniles less attention is given to rainbow trout broodstocks and especially neomales that are used to produce all-female population. In a previous study we were able to demonstrate that a short carbohydrate intake (two-day feeding) did not induce specific metabolic changes in the liver of females, males and neomales broodstocks [13]. Moreover, we also demonstrated that neomales displayed more pronounced modifications of glucose and lipid metabolisms in response to nutritional status or HC diet compared to both females and males broodstocks.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, we demonstrated that a short period of glucose intake (two day -5 meals) did not induce specific metabolic in mature female and male and neomale [13]. However, compared to both mature females and males, neomales displayed more pronounced modifications of their metabolism in response to nutritional status and HC diet (especially a huge increase in Gck mRNA levels) [13]. Although this could be attributed to their physiological status and weight close to juveniles during the experiment, it cannot be excluded that neomales are better user of high carbohydrate diet compared to juveniles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fish have poor absorption capacity for dietary carbohydrates. They are susceptible to prolonged hyperglycemia, excessive hepatic lipid accumulation, growth retardation, and decreased immune function after long-term highcarbohydrate diet feeding [6][7][8]. Researchers used [U-14C] glucose as a tracer to prove that ingested glucose is synthesized into glycogen stored in fish livers [9].…”
Section: Introductionmentioning
confidence: 99%